The role of species traits for grassland productivity. Issue 7 (27th July 2020) - Taubert, Franziska; Hetzer, Jessica; Schmid, Julia S.; Huth, Andreas
Abstract: The relation between species diversity and ecosystem functioning is one of the most frequently discussed topics in ecology. Experiments often revealed an increase of productivity in species‐rich ecosystems. But large variations in these relationships, both on a local scale and in comparisons of sites along environmental gradients, still challenge our understanding of the role of species (with specific traits) and their interactions in ecosystems. In this study, we explored the role of species traits for ecosystem functioning. We used an individual‐based mechanistic grassland model which captures intra‐ and interspecific competition between plants for light and soil resources. We explored how the dynamics and productivity of grasslands are influenced by species traits and analyzed in a simulation study two species, which differ only in one particular trait. Our focus was on traits that determine how species can cope with resource limitations, for which we identified their relative importance for (1) individual plant growth, (2) monoculture dynamics, and (3) species mixture dynamics. We observed diverse relationships between species traits and different vegetation attributes for the different ecosystem levels. Most traits showed positive but saturating trends of increasing trait values but the variability in these relations increased in monocultures with intraspecific plant interactions and even more pronounced in mixtures with interspecific interactions. Using a process‐based grassland model, we were able to simulate overyielding even though it was not correlated with trait values or trait differences between both species. Correlations were also not found in terms of stability of vegetation dynamics. In contrast, for some traits already small differences supported the dominance of a species in the mixture in which species dynamics generally followed trade‐offs. The here presented simulation study demonstrates the use of process‐based models for analyzing trait‐productivity relationships in grasslands. Such models can complement previous approaches in empirical and theoretical biodiversity research and can help to move closer to understanding the mechanisms governing grassland dynamics.